Ponderal Substituent Effect due to Alkyl Substitution in 1-Alkanes: Quantitative Correlation with Physical Constants - Jessy, J.M. (Asian Journal of Chemistry, 2010)
Ponderal substituent effect due to changing alkyl substitution is demonstrated on the physical properties-vapour pressure, viscosity, diamagnetic susceptibility and polarizability-of 1-alkanes. The ponderal parameter log (1/μ) has been shown to give linear correlation with a function of the corresponding physical constant, in each case. The correlation is justified as consequence of substituent mass effect on the vibrational component of the covalent molecular interactions between the alkane molecules, created by dispersion forces.